Comparative evaluation of carcass traits and meat quality in native Aseel chickens and commercial broilers. Issue 3 (3rd May 2016) - Rajkumar, U.; Muthukumar, M.; Haunshi, S.; Niranjan, M.; Raju, M. V. L. N.; Rama Rao, S. V.; Chatterjee, R. N.
Abstract: A comprehensive study was conducted to analyse the meat quality attributes, composition and carcass traits in Aseel chickens and commercial broilers at market age on the basis of physiological age. A total of 20 Aseel (26 and 56 weeks) and 20 broiler (6 weeks) chickens were divided into two groups on a live weight basis, i.e. large (≥2.5 kg) and small (<2.5 kg) with 10 birds in each subgroup. The pH of meat did not show any significant variation between Aseel and broiler chickens. The meat from heavier birds had significantly higher pH. Shear force value and hydroxyproline contents were significantly higher in Aseel chickens. Aseel birds had significantly higher red (a*) colouration and lower lightness (L*) than broiler chickens. The texture and acceptability of Aseel meat were significantly higher. Scanning electron microscopy revealed that muscle fibres in Aseels were arranged in a more coiled pattern making the muscle tough. A larger amount of connective tissue was also observed between the muscle fibres compared with the broiler chickens. The dressing percentage was significantly higher in larger chickens. Commercial broilers recorded significantly higher meat proportion and lower proportion of bone. The meat:bone ratio was 1.07:1.0 in Aseel and 1.31–1.0 in broiler chicken. Breast muscle content was significantly lower in smaller Aseel chickens. Aseel chicken had stronger and heavier backs and shanks. Abdominal fat percentage was significantly lower in Aseel (0.73–0.78%). The study concluded that the firm texture of Aseel meat was due to the high collagen content and interlocking connective tissue between the muscle fibres. The texture and acceptability of Aseel meat was higher. Aseel cocks had strong legs, lean meat and less abdominal fat, making them a high-value meat bird in addition to their aggressive fighting ability.